Self-Diagnosis in Relation to Help-Seeking Behavior and Health Literacy among Adolescents in Indonesia - Ayub Firmansyah; Rr. Dwi Astuti (Journal of Educational Sciences, 2026)
Mental health self-diagnosis among adolescents has increased alongside the widespread use of digital health information. This study examined the relationships between help-seeking behavior, health literacy, and self-diagnosis among adolescents in Indonesia. A quantitative cross-sectional correlational design was employed. Using purposive sampling, 157 respondents aged 15-24 years who had accessed mental health information through digital media completed online Likert-type scales. Because the data were non-normally distributed and contained relevant extreme outliers, the hypotheses were tested using Spearman's rho correlation. The results showed a strong positive relationship between help-seeking behavior and self-diagnosis (r_s = .748, p < .001) and a moderate positive relationship between health literacy and self-diagnosis (r_s = .462, p < .001). The direction of these relationships differed from the initial hypotheses. These findings suggest that self-diagnosis may function as an initial interpretive step in adolescents' efforts to understand their condition and seek information or assistance. Nevertheless, self-assessment should not replace professional evaluation. These findings can support the development of adolescent digital mental health literacy programs that encourage critical evaluation of online information and responsible help-seeking.